given that ![a \: sinB + b \: sinB = c \: a \: sinB + b \: sinB = c \:](https://tex.z-dn.net/?f=a+%5C%3A+sinB+%2B+b+%5C%3A+sinB+%3D+c+%5C%3A+)
prove:
![= > ({a \: cosB - b \: sinB}) = \sqrt{ {a}^{2} + {b}^{2} - {c}^{2}.} = > ({a \: cosB - b \: sinB}) = \sqrt{ {a}^{2} + {b}^{2} - {c}^{2}.}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%28%7Ba+%5C%3A+cosB+-+b+%5C%3A+sinB%7D%29+%3D+%5Csqrt%7B+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+-+%7Bc%7D%5E%7B2%7D.%7D+)
Answers
Answered by
0
Solution:
It is given that
Squaring both sides,
Hence, it is proved.
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d4c/f694090db35d6cc4be3288d4f2f870e1.jpg)
Similar questions